Profile of aripiprazole in the treatment of bipolar disorder in children and adolescents - Kirino E (Dove Medical Press, 2014)
Eiji Kirino1–3 1Department of Psychiatry, Juntendo University School of Medicine, 2Department of Psychiatry, Juntendo University Shizuoka Hospital, 3Juntendo Institute of Mental Health, Shizuoka, Japan Abstract: Bipolar disorder is a pernicious illness. Compared with the later-onset form, early onset bipolar disorder is associated with worse psychosocial outcomes, and is characterized by rapid cycling and increased risks of substance abuse and suicide attempts. Controlling mood episodes and preventing relapse in this group of pediatric patients requires careful treatment. Here, we review the effectiveness of aripiprazole for bipolar disorder in children and adolescents, with discussion of this drug's unique pharmacological profile and various clinical study outcomes. Aripiprazole acts as a serotonin 5-HT2A receptor antagonist, as well as a partial agonist of the serotonin 5-HT1A and dopamine D2 receptors. It can be safely used in children and adolescents, as it is highly tolerated and shows lower rates of the side effects typically observed with other antipsychotic drugs, including sedation, weight gain, hyperprolactinemia, and extrapyramidal syndrome. The presently reviewed randomized controlled trials (RCTs) and non-RCTs generally reported aripiprazole to be effective and well-tolerated in children and adolescents with bipolar disorder. However, due to the limited number of RCTs, the present conclusions must be evaluated cautiously. Furthermore, aripiprazole cannot yet be considered a preferred treatment for children and adolescents with bipolar disorder, as there is not yet evidence that aripiprazole shows greater efficacy compared to other second-generation antipsychotics. Additional data are needed from future head-to-head comparison studies. Keywords: child, mania, mixed state